Feasibility of biodiesel production from patty oil waste via the transesterification - Nur Syahirah, Salehhuddin; Muhammad Nor Fazli, Abd Malek; Maniam, Gaanty Pragas (Penerbit Universiti Malaysia Pahang, 2024)
Patty oil waste poses significant environmental risks, including land contamination, water pollution, and detrimental effects on plant and animal life if not managed appropriately. To address this issue, the transesterification process offers a sustainable solution for converting patty oil waste into biodiesel, an eco-friendly alternative fuel. This study aims to optimize biodiesel production from patty oil waste using a two-step transesterification process, evaluating its physical and chemical properties. The solid-phase patty oil waste was pretreated and processed using potassium hydroxide (KOH) as a homogeneous catalyst. The initial free fatty acid (FFA) content of the patty oil waste was 6.175%, exceeding the acceptable 5% threshold for direct transesterification. After esterification, the FFA content was reduced to 1.238%, meeting the required specifications. Biodiesel properties were characterized using thin-layer chromatography (TLC) and gas chromatography-mass spectrometry (GC-MS), confirming high methyl ester conversion. The optimal reaction conditions were determined as a KOH concentration of 1.5 wt%, a reaction time of 90 minutes, and a methanol-to-oil molar ratio of 6:1, yielding a maximum methyl ester conversion of 88.47%. The produced biodiesel exhibited properties in compliance with ASTM D6571 standards, including a density of 854 kg/m³, iodine value of 81.24 g/100 g, and acid value of 0.0314 mg KOH/g. This study highlights the potential of patty oil waste as a feedstock for biodiesel production and underscores the efficacy of RSM in optimizing the transesterification process for high-quality biodiesel yield.